GENERALIZED PASCAL’S TRIANGLE AND METALLIC RATIOS - Sivaraman, R. (International Journal of Research -GRANTHAALAYAH, 2021)
In this paper, I had demonstrated the way to determine the sequence of metallic ratios by generalizing the usual Pascal’s triangle. In doing so, I found several interesting properties that had been discussed in detail in this paper. I had proved four new results upon generalizing Pascal’s triangle. Thus, the primary aim of this paper is to connect the idea of Generalized Pascal’s triangle with that to the sequence of metallic ratios.